Development and validation of a sensitive assay for analysis of midazolam, free and conjugated 1-hydroxymidazolam and 4-hydroxymidazolam in pediatric plasma: Application to Pediatric Pharmacokinetic Study - Moorthy, Ganesh S. (J Chromatogr B Analyt Technol Biomed Life Sci, 2017)
Pharmacokinetic, pharmacodynamic and pharmacogenomic studies of midazolam are currently being performed in critically ill children to find suitable dose regimens. Sensitive assays using small volumes of plasma are necessary to determine the concentrations of midazolam and its respective metabolites in pediatric studies. Midazolam is metabolized to hydroxylated midazolam isomers, which are present as free as well as the corresponding glucuronide conjugates. A high-performance liquid chromatographic method with tandem mass spectrometry has been developed and validated for the quantification of midazolam, and free and total 1-hydroxymidazolam and 4-hydroxymidazolam metabolites in small volumes of plasma. Cleanup consisted of 96-well µ-elution solid phase extraction (SPE). The analytes were separated by gradient elution using a C(18) analytical column with a total run time of 5 min. Multiple reaction monitoring was employed using precursor to product ion transitions of m/z 326.2 →291.3 for midazolam, m/z 342.1 →203.0 for 1-hydroxymidazolam, m/z 342.1 →325.1 for 4-hydroxymidazolam and m/z 330.2 →295.3 for (2)H(4)-midazolam (internal standard). Since authentic hydroxymidazolamglucuronide standards are not available, samples were hydrolyzed with β-glucuronidase under optimized conditions. Assay conditions were modified and optimized to provide appropriate recovery and stability because 4-hydroxymidazolam was very acid sensitive. Standard curves were linear from 0.5 to 1,000 ng/mL for all three analytes. Intra- and inter day accuracy and precision for quality control samples (2, 20, 200 and 800 ng/mL) were within 85–115% and 15% (coefficient of variation), respectively. Stability in plasma and extracts were sufficient under assay conditions. Plasma samples were processed and analyzed for midazolam, and free 1-hydroxymidazolam and 4-hydroxymidazolam metabolites. Plasma samples that were hydrolyzed with β-glucuronidase were processed and analyzed for midazolam, and total 1-hydroxymidazolam and 4-hydroxymidazolam metabolites under the same assay conditions. The difference in concentration between the total and free hydroxymidazolam metabolites provided an estimate of conjugated hydroxymidazolam metabolites. The combination of 96-well µ-elution SPE and LC-MS/MS allows reliable quantification of midazolam and its metabolites in small volumes of plasma for pediatric patients. This assay is currently being successfully utilized for analysis of samples from ongoing clinical trials.